Effect of a platelet activating factor antagonist, WEB 2086, on allergen induced asthmatic responses. - Freitag, A (1993)
BACKGROUND--Platelet activating factor (PAF) has been implicated in the pathogenesis of airway hyperresponsiveness in asthma. The purpose of this study was to evaluate the effects of a selective PAF antagonist (WEB 2086), given in doses known to antagonise the effects of inhaled PAF in human subjects, on allergen induced early and late asthmatic responses and on airway hyperresponsiveness. METHODS--Eight atopic, mildly asthmatic subjects were studied during a screening period and two treatment periods. During the screening period subjects inhaled an allergen to which they were known to be sensitised and the response was measured as the fall in the forced expired volume in one second (FEV1) to show the presence of early (0-1 h) and late (3-7 h) asthmatic responses. On another day the subjects inhaled allergen diluent. During the treatment periods subjects inhaled allergen after one week's pretreatment with WEB 2086 (100 mg three times a day) or placebo administered in a randomised, double blind, crossover fashion. Histamine airway responsiveness was measured 24 hours before and 24 hours after allergen and the results were expressed as the provocative concentration causing a 20% fall in FEV1 (PC20). RESULTS--The maximal early asthmatic response after allergen with placebo treatment was 18.4% (SE 4.4%) and with WEB 2086 18.9% (4.4%). The maximal late response with placebo treatment was 21.7% (5.3%) and with WEB 2086 21.2% (3.0%). The log difference (before and after allergen) in histamine PC20 was 0.35 (0.06) after placebo treatment and 0.30 (0.1) after WEB 2086. CONCLUSIONS--These results indicate that one week of treatment with an orally administered PAF antagonist (WEB 2086) does not attenuate allergen induced early or late responses or airway hyperresponsiveness.